Răspuns :
Explicație pas cu pas:
[tex]f(x) = - x^{2} - 8x - 7[/tex]
se rezolvă ecuația atașată funcției:
[tex]- x^{2} - 8x - 7 = 0 \\ - (x^{2} + 8x + 7) = 0 \\ - (x + 7)(x + 1) = 0[/tex]
[tex] = > x = -7;x=-1[/tex]
[tex]a = - 1;b = - 8;c = - 7[/tex]
[tex]Δ = {( - 8)}^{2} - 4( - 1)( - 7) = 64 - 28 = 36[/tex]
[tex] - \frac{Δ}{4a} = - \frac{36}{4( - 1)} = 9 [/tex]
[tex] = > Imf = (- \infty ;9][/tex]
[tex] - \frac{b}{2a} = - \frac{ - 8}{2( - 1)} = - 4 [/tex]
a<0 => funcția are un punct de maxim
[tex]V( -\frac{b}{2a};-\frac{Δ}{4a})=V( - 4;9)[/tex]
f(x) crescătoare, x ∈ (-∞; -4)
f(x) descrescătoare, x ∈ (-4; +∞)